Impact of using Double Layers Perforated Liners on the Acoustic Treatments of the Combustor Systems - Hacham, Wisam S.; Hiji, Faisal S. (Al-Khwarizmi Engineering Journal, 2020)
The response of the combustor’s liner to the air-flow that passes through it is the key reason for the combustion chambers noise, hence the instabilities of those chambers that decreases the mechanical efficiency of such sections, by increased its mechanical vibrations, which increases the failure rate created during originating of the cracks spreading by the shakes producing by the series of high-level frequencies. Accordingly, any work debating the impact of the context of liners in the combustion chamber can provide grasping for the combustion noise generated by the undesirable vibrations, and benefits the industrial firms to design an ideal production procedure which increases the lifespan of the combustor. The goal of this work is to examine the influence of the acoustic treatment using a double layers cylindrical perforated liner on the acoustic transmission loss of gas turbines. The liners layout influences on this acoustic parameter was examined using an experimental data gained by the insertion of a full scale single and double patterns of perforated liners into the unique large scale acoustic wind tunnel at the acoustic research center at Hull University. The experimental tests under-designed acoustic signals were established firstly using 0m/s air cross-flow velocity, then by changed velocities with interval 5m/s ranging between 10m/s to 25m/s. MATLAB script was used to simulate, analyze, and figure out the data collected the insertion of single and double layer patterns of the perforated liner. The experiments demonstrated that, if the perforation acoustic treatments are applied, the acoustic transmission loss will decrease, particularly obvious at higher level frequencies. Further, the results exposed that the air tunnel with the insertion of the liner with double layers reveals an improved perforation acoustic treatment.